Development of an Android mobile application for cycle users of the city of Bogotá D.C. - Paz Penagos, Hernán (LACCEI Latin American and Caribbean Consortium of Engineering Institutions, 2017)
This article is about the development of an application for smartphone phones with Android operating system for cycle route who transit in the city of Bogota D.C. The development of the project was achieved with the help of a methodological process, which was structured in four phases, these phases are described: the general context of applications developed in Android, needs identification of cyclical, mobile application development, validation and results; The coupling of these stages allowed to analyze the current situation and to design, program and implement an application according to the needs of the study population, in order to encourage the use of the bicycle as a means of transport for sustainable mobility. The application developed includes the following functionalities: georeferenced maps of the network of cycle route and bicycle route of the city of Bogota, by selecting a source point and a destination point a route is generated, which is drawn on a map, which has in The possibility of users having information on the status of the cycle route through the qualification of the state of the road, lighting and signaling, search for parking cycle, creation of public or private points of interest such as bicycle stores, Workshops of repair, hydration points, among others, history of the route made with information of the time spent in making the route and access to the information of events and tips.

Este artículo trata sobre el desarrollo de una aplicación para teléfonos inteligentes con sistema operativo Android para ciclovías que transitan en la ciudad de Bogotá DC El desarrollo del proyecto se logró con la ayuda de un proceso metodológico, el cual se estructuró en cuatro fases, estas Se describen las fases: contexto general de las aplicaciones desarrolladas en Android, identificación de necesidades cíclicas, desarrollo de aplicaciones móviles, validación y resultados; El acoplamiento de estas etapas permitió analizar la situación actual y diseñar, programar e implementar una aplicación acorde a las necesidades de la población de estudio, con el fin de incentivar el uso de la bicicleta como medio de transporte para la movilidad sostenible. La aplicación desarrollada incluye las siguientes funcionalidades.
Keywords: Aplicaciones móviles; Ciclovías; Bicycle trails; Android; Mobile app; Cycle route; Google maps; Bogotá